[OP.1C.05] THE POLISH REGISTRY FOR FIBROMUSCULAR DYSPLASIA - THE PRELIMINARY REPORT ON DISTRIBUTION OF VASCULAR BED INVOLVEMENT AND COMPLICATIONS IN PATIENTS ENROLLED IN ARCADIA-POL STUDY. (September 2016) - Warchol-celinska, E.; Hanus, K.; Talarowska, P.; Florczak, E.; Jozwik-plebanek, K.; Januszewicz, M.; Michalowska, I.; Prejbisz, A.; Wojcik, W.; Janaszek-sitkowska, H.; Makowiecka-ciesla, M.; Stryczynski, L.; et al.
Abstract : Objective: To present preliminary evaluation of vascular bed involvement and vascular complications in patients with fibromuscular dysplasia (FMD) enrolled to ARCADIA-POL registry. Design and method: The first 84 patients (59F[70.2%], 25M[29.8%], mean age: 42.5 ± 14.8 years, range:18–72) with confirmed FMD in any vascular bed were enrolled in 2015 in ARCADIA-POL registry (instituted on the basis of as Polish-French collaboration). A standardized FMD data form was used for data collection. All patients underwent detailed clinical evaluation including ambulatory blood pressure monitoring (ABPM), biochemical evaluation, biobanking, duplex Doppler of carotid and abdominal arteries and whole body angio-CT. Results: In the analyzed group FMD was identified in renal arteries in 74 (88.1%) patients, bilaterally in 29 (39.2%) patients as well as in carotid, intracranial and vertebral arteries in 14 (16.7%), 14 (16.7%) and 6 (7.1%) patients, respectively. FMD was also identified in celiac trunk and mesenteric, iliac and splenic arteries in 12(14.3 %), 7(8.3%), and 6(7.1%) patients, respectively. Evaluating degree of renal artery stenosis on duplex Doppler and angio-CT, significant stenosis was identified in 19 (25.7%) patients (in this group 8 patients had restenosis after previous intervention) whereas non-significant stenosis was found in 55 (74.3%) patients (in this group 9 patients had a history of intervention on renal artery). In 39 patients (46.4%) FMD was identified in two or more vascular bed. Two vascular beds were involved in 31% (26 pts), three in 11.9% (10 pts), four in 2.4 % (2 pts) and five in 1.2 % (1 pt). Arterial dissection(s) and aneurysms in various vascular beds were found in 14.3% and 26.2% of patients respectively. Severe FMD defined as first onset of FMD <30 years, affecting at least 3 vascular beds complicated with thrombosis or dissection requiring an endovascular or surgical repair, with no inflammatory background was identified in 2 patients (2.4%). Conclusions: Preliminary data of ARCADIA-POL registry showed that renal FMD was the most frequent, but also cerebrovascular FMD occurred in relatively large proportion of patients. Our data revealed high incidence of FMD lesions coexisting in different vascular beds as well as relatively frequent occurrence of vascular complications.